Analysis of the Features of the Vernacular Plank Houses of the Qiang Ethnic Group in Southern Songpan County: A Case Study of Xiaoxinggou - Li Yingtao；Ma Zhitao (Contemporary Social Sciences, 2021)
The Qiang ethnic group in southern Songpan county lives in vernacular plank houses (VPHs) with an architectural tradition that dates to the period of the ancient Di people. VPHs are now mainly constructed in settlements of ethnic groups such as Baima Tibetans, Amdo Tibetans, and the Qiang people living in Wenxian county, Longnan city of Gansu province, and Maoxian, Lixian, Wenchuan, and Beichuan of Sichuan province respectively. Although VPHs of the Qiang people living in southern Songpan share many similarities with those of adjacent Tibetans in structure, construction, and spatial layout, they feature the Qiang people’s unique architectural culture, and reflect a style transition from VPHs in the north to blockhouses in the south. The VPHs, as represented by those in Xiaoxinggou, play a significant role in the diversified architectural culture of this ethnic group. Their unique cultural value is worthy of further exploration and protection.